Thuemenella cubispora (Ascomycetes, Xylariaceae), un hongo poco común en México - Medel, Rosario (Instituto de Ecología, A.C., 2001)
Thuemenella cubispora is a fungus widely distributed in the world but rarely collected in Mexico (only known from the state of Morelos). Here the species is recorded for first time from the state of Quintana Roo and additional information about stroma size as well as a description under electron microscopy is provided.